Risk of Readmission Among HIV Patients in Public Portuguese Hospitals: Longitudinal Multilevel Population-Based Study - Shaaban, Ahmed N.; Dias, Sara S.; Muggli, Zelia; Peleteiro, Bárbara; Martins, Maria Rosario O. (Frontiers in Public Health, 2020)
Background: Thirty-day hospital readmission is receiving growing attention as an indicator of the quality of hospital care. Understanding factors associated with 30-day hospital readmission among HIV patients in Portugal is essential given the high burden cost of HIV hospitalizations in Portugal, a country suffering from financial constrains for almost 10 years. Objectives: We aimed to estimate the thirty-day hospital readmission rates among HIV patients in Portugal and to identify its determinants using population based data for Portuguese public hospitals. Study design: A multilevel longitudinal population-based study. Methods: Between January 2009 and December 2014 a total of 37,134 registered discharges in the Portuguese National Health Service (NHS) facilities with HIV/AIDS as a main or secondary cause of admission were analyzed. Logistic regression was used to compare 30-day hospital readmission categories by computing odds ratio (OR) and corresponding 95% confidence intervals (95%CI). A normal random effects model was used to determine unmeasured factors specific to each hospital. Results: A total of 4,914 (13.2%, 95%CI: 12.9%-13.6%) of the hospitalizations had a subsequent 30-day readmission. Hospitalizations that included exit against medical opinion (OR=1.18, 95%CI: 1.01-1.39), scheduled admissions (OR=1.71, 95%CI: 1.58-1.85) and tuberculosis infection (OR=1.20, 95%CI: 1.05-1.38) exhibited a higher risk of hospitalizations with subsequent 30-day readmission. On the contrary, hospitalizations that included females (OR=0.87, 95% CI: 0.81-0.94), a transfer to another facility (OR=0.78, 95%CI: 0.67-0.91) and having a responsible financial institution (OR=0.63, 95%CI: 0.55-0.72) exhibited a lower risk of hospitalizations with subsequent 30-day readmission. Hospitalizations associated with higher number of diagnosis, older ages, or hospitalizations during the economic crisis showed an increasing trend of 30-day readmission, whereas an opposite trend was observed for hospitalizations with higher number of procedures. Significant differences exist between hospitals quality, adjusting for other factors. Conclusion This study analyses the indicators of thirty-day hospital readmission among HIV patients in Portugal and provides useful information for enlightening policymakers and health care providers for developing health policies that can reduce costs associated with HIV hospitalizations.